Are elastic liposomes better for skin delivery of therapeutic molecules? - Jahan, Fatima Naushin (Curtin University, 2011)
The objectives of the present study were to design and evaluate elastic liposomes in comparison to simple drug solution and conventional liposomes, and in delivering a model NSAID, Ibuprofen (IBU) across human epidermis after topical application. The scope of the project included formulation development, characterization, and optimization based on their physical characteristics and determination of IBU penetration when incorporated in conventional and elastic liposomes through human epidermis after topical application, and finally to establish the relationship between the formulation variables and skin penetration of IBU loaded liposomes.